Clinical Outcome of Arthroscopic Management of Mucoid Degeneration of Anterior Cruciate Ligament - Madan Mohan Ballal; K. J. C. Chidanand; Vijendra Yadav; Akshay Dhanda; Chetan Nagaraja; Sachin K. Gowda (Journal of the Scientific Society)
Introduction: Mucoid degeneration of the anterior cruciate ligament (MDACL) is a poorly understood entity. The collection of mucinous material in the substance of anterior cruciate ligament (ACL) produces pain and thus limits motion in the knee. This study involves clinic-radiological presentation of patients with mucoid ACL, arthroscopic de-bulking of ACL and outcomes. Materials and Methods: Between September 2021 and October 2022, 24 patients were diagnosed with MDACL. All cases were examined clinically followed by magnetic resonance imaging (MRI) then confirmed by arthroscopy findings and then were sent for histopathology reporting. Clinical data, including pain location, terminal flexion or extension pain, range of motion, Lysholm knee score, and International Knee Documentation Committee score, were assessed pre- and postoperatively. MRI showing an increased signal of the ACL in T1-and T2-weighted images was reported as mucoid degeneration of the ACL by the radiologist. Upon arthroscopy, the ACL had a homogenous, bulbous, hypertrophied, and taut appearance occupying most of the intercondylar notch space. Debulking of the ACL was performed by excision of the degenerated mucoid tissue, leaving behind as much of the intact ACL as possible, and notchplasty helped prevent impingement of the ACL against the roof and lateral wall. Unfortunately, in 4 (16.67%) patients, we had to reconstruct the ligament due to the ACL insufficiency to stabilize the knee. Results: Thirteen patients were males (54.17%), and eleven (45.83%) patients were females, with a mean age of 36.7 years for males (range 19–63 years) and 41.7 years for females (range 28–73 years). All patients had pain in deep flexion, with 70.8% (n = 1 7) reporting trivial trauma before the onset of symptoms. On terminal flexion/extension, pain relief was obtained in 19 of 20 knees, ranging from good to excellent. Stability tests for ACL showed a firm endpoint in all. GNRB arthrometer examination revealed a tibial translation comparable to the noninvolved side, and 85% (n = 20) showed good to excellent subjective satisfaction. Conclusions: Prior knowledge of the condition with a high suspicion index and careful MRI interpretation can establish the diagnosis preoperatively. They respond well to a judicious arthroscopic debulking of the ACL with or without notchplasty, improving patient satisfaction and function without causing clinical instability in daily activities. However, young patients should be forewarned about the risk of instability, and the necessity of ACL reconstruction in the future.